Risk-based sensor scheduling for target detection. (July 2019) - Pang, Ce; Shan, Ganlin
Abstract: A risk-based sensor scheduling method is proposed and applied to target detection in this paper. This paper mainly focuses on the sensor radiation interception risk and target detection risk. Firstly, the general risk-based sensor scheduling model is established; Secondly, the target detection risk model and sensor radiation risk model are proposed respectively. It is stressed that the radiation interception model is based on Partially Observed Markov Decision Process (POMDP) due to the reason that parameters of the enemy's radiation receiver are not accessible to calculate the radiation interception risk directly; Furthermore, combined with double-roulette, the basic artificial bee colony (ABC) is improved to get sensor scheduling schemes from the objective function; Ultimately, simulations are conducted and indicate that the models and the algorithm in the paper possess some advantages over existing ones.